Lethal Male Combat of Anastatus japonicus (Hymenoptera: Eupelmidae), an Egg Parasitoid of Lepidopterous and Hemipterous Pests - Muhammad Yasir Ali; Gonzalo A. Avila; Zheng-Yu Luo; Muhammad Asghar Hassan; Khalid Ali Khan; Jin-Ping Zhang; Feng Zhang (Insects, 2025)
Aggressive interactions between males are common when victors gain increased mating success but can result in severe injury or death for the defeated. Anastatus japonicus (Hymenoptera: Eupelmidae) is a solitary egg parasitoid of hemipteran and lepidopteran species. Here, we investigated lethal interactions between A. japonicus males and analyzed aggression behavior scaled with the male condition, number of competitors, number of presented females, and female mating status. The intensity of A. japonicus male aggressiveness increased with the number of competitors and the number of presented females but was not affected by male relatedness. The intensity and frequency of A. japonicus male aggressive interactions were greater when males competed for virgin females compared to mated females. Larger A. japonicus males won more contests than smaller males and honey-fed males defeated starved ones, where defeated males suffered the loss of appendages and/or died. Fighting appeared to be the norm in all-male groupings, regardless of the presence of females. A number of biological and ecological factors are deducted that likely contribute to the evolution of male aggressive behavior in A. japonicus.